2018
DOI: 10.3390/s18113949
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Robot–World and Hand–Eye Calibration without a Calibration Object

Abstract: An extended robot–world and hand–eye calibration method is proposed in this paper to evaluate the transformation relationship between the camera and robot device. This approach could be performed for mobile or medical robotics applications, where precise, expensive, or unsterile calibration objects, or enough movement space, cannot be made available at the work site. Firstly, a mathematical model is established to formulate the robot-gripper-to-camera rigid transformation and robot-base-to-world rigid transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
(46 reference statements)
0
22
0
1
Order By: Relevance
“…However, the number of poses and camera resolution remain almost same. It can be observed that the method by Shah [8] provides a better distribution of the rotational error and hence has the lowest relative rotation error ( ) values, while the method by Li et al [9] yields a comparable result. The lowest relative translation error ( ) varies for both datasets and is yielded by the proposed method Xc2 and Park and Martin [31].…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…However, the number of poses and camera resolution remain almost same. It can be observed that the method by Shah [8] provides a better distribution of the rotational error and hence has the lowest relative rotation error ( ) values, while the method by Li et al [9] yields a comparable result. The lowest relative translation error ( ) varies for both datasets and is yielded by the proposed method Xc2 and Park and Martin [31].…”
Section: Resultsmentioning
confidence: 94%
“…Many researchers favor this approach since the calibration pattern is easy to acquire and its use yields good results. In contrast, some studies [22,23] prefer Structure from Motion (SFM) to acquire the relative camera transformation when the camera is moved from one point to another. The approach is independent of the calibration pattern and can acquire the correspondences from the feature-rich environment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers favor this approach since the calibration pattern is easy to acquire and its use yields good results. In contrast, some studies [23,24] prefer Structure from Motion (SFM) to acquire the relative camera transformation when the camera is moved from one point to another. The approach is independent of the calibration pattern and can acquire the correspondences from the feature-rich environment.…”
Section: Methodsmentioning
confidence: 99%